Conjunctival Lesions: When Should We Perform Biopsy? - Khan, Lubna; Malukani, Malukani; Saxena, Ankur (Nepalese Journal of Ophthalmology, 2018)
Introduction: The conjunctiva is a thin and flexible mucus membrane that provides a protective barrier for the eye. Very few histopathologic studies have been conducted on biopsies from conjunctival lesions (CL) in central India. Objective: To study the spectrum of CL and define those lesions that need attention with regard to need of biopsy in order to prevent grave sequelae and ocular morbidity. Results: Degenerative conditions such as pterygium followed by pinguicula were the commonest lesions seen in conjunctiva. Out of 129 subjects, youngest in the series was 3 years old while oldest patient was 72 years of age. Commonest age interval for involvement was 35 to 50 years. In children below 8 years, cystic lesions (infective or inclusion), limbal dermoid and choristoma were seen. Vascular lesions were noticed by patients for the first time between mid-teens to 25 years age. Premalignant lesions were dysplasia, actinic keratosis and PAM with or without XP. Malignant lesions in this series were squamous cell carcinoma, basal cell carcinoma and sebaceous carcinoma; which were observed in the age interval 25 to 75 years. In none of the malignant conditions there was deeper penetration into the globe or orbit. Though diagnosed within two weeks duration (by incisional biopsy) from appearance of nodule, unfavourable outcome was seen only in one malignant CL; a case having sebaceous carcinoma. In all pediatric cases outcome was good, except in child having choristoma, where amblyopia ensued before a diagnosis was made. Response to sclerotherapy was excellent as all the epibulbar vascular malformations regressed. All degenerative lesions regressed except one recurrence in a recurred pterygium. Case diagnosed as large B cell lymphoma recurred after one year. Dysplastic changes were seen to occur at limbus on followup in one XP, but in all cases of naevi, neither cellular atypia was seen nor melanoma developed. Conclusion: An overview of various CL disclosed that clinician has to differentiate benign from premalignant and malignant lesions. Early diagnosis, proper histological study and patient education, all are equally important for achieving good outcome.